Embracing The Change: Personal Experience in Academic Unit Transformation - Hazem Said (Academic Chairpersons Conference Proceedings, 2023)
This presentation will cover personal experience and case study on how academic unit head can embrace change, build an identity for their unit, and lead their faculty and staff in transforming their unit from obscurity to prominence while under budget constraints and limited authority.
Keywords: Change; Leadership; Transformation; Delegation; Growth